Kepemimpinan Pembelajaran untuk Mencapai Program Unggulan Tahfidz di SMPIT TQ Ulil Albab Karanganyar - Irwan Saputra; Thitha Meista Mulya Kusuma; Giri Sayekto; Wafrotur Rohmah; Darsinah Darsinah (Journal on Education, 2024)
Instructional leadership plays a vital role in the success of the tahfidz flagship program at SMPIT TQ Ulil Albab Karanganyar. This study aims to analyze the role of leadership in achieving the tahfidz program's goals and identify the challenges and solutions faced. Using a qualitative approach, data were collected through in-depth interviews and observations of the principal, teachers, students, and parents. The results show that effective leadership can create a clear vision, support teachers in professional development, and ensure parental involvement. A well-structured tahfidz program enhances students' religious competence and the school's competitiveness. Challenges such as differences in students' initial abilities and consistency among tahfidz teachers can be addressed through initial assessment, personalized approaches, and management support.